Sex Difference in the Tolerance of Hepatic Ischemia-reperfusion Injury and Hepatic Estrogen Receptor Expression According to Age and Macrosteatosis in Healthy Living Liver Donors. Issue 2 (February 2022) - Han, Sangbin; Cho, Junhun; Wi, Wongook; Won Lee, Kyo; Hwa Cha, Hyun; Lee, Sanghoon; Hyun Ahn, Joong; Kim, Seonwoo; Sung Choi, Gyu; Man Kim, Jong; Ha, Sang Yun; Soo Kim, Gaab; et al.
Abstract : Background: Hepatic estrogen signaling, which is important in liver injury/recovery, is determined by the level of systemic estrogen and hepatic estrogen receptor. We aimed to evaluate whether females' advantage in the tolerance of hepatic ischemia-reperfusion injury decreases according to the age of 40 y (systemic estrogen decrease) and macrosteatosis (hepatic estrogen receptor decrease). Methods: We included 358 living liver donors (128 female and 230 male individuals). The tolerance of hepatic ischemia-reperfusion injury was determined by the slope of the linear regression line modeling the relationship between the duration of intraoperative hepatic ischemia and the peak postoperative transaminase level. Estrogen receptor content was measured in the biopsied liver samples using immunohistochemistry. Results: In the whole cohort, the regression slope for aspartate transaminase was comparable between female and male individuals ( P = 0.940). Within the subgroup of donors aged ⩽40 y, the regression slope was significantly smaller in female individuals ( P = 0.031), whereas it was comparable within donors aged >40 y ( P = 0.867). Within the subgroup of nonmacrosteatotic donors aged ⩽40 y, the regression slope was significantly smaller in female individuals in univariable ( P = 0.002) and multivariable analysis ( P = 0.006), whereas the sex difference was not found within macrosteatotic donors aged ⩽40 y ( P = 0.685). Estrogen receptor content was significantly greater in female individuals within nonmacrosteatotic donors aged ⩽40 y ( P = 0.021), whereas it was not different in others of age >40 y or with macrosteatosis ( P = 0.450). Conclusions: The tolerance of hepatic ischemia-reperfusion injury was greater in female individuals than in male individuals only when they were <40 y and without macrosteatosis. The results were in agreement with the hepatic estrogen receptor immunohistochemistry study. Abstract : Supplemental Digital Content is available in the text.